Current Account And Financial Account: Push Or Finance? - Audrey, Liwan; Lau, Evan; FU, Nelson; Oh, Swee-Ling (2008)
The purpose of this paper is to empirically investigate the causality pattern between current account (CA) with the components in financial account (FA) for the four crisis-affected Asian countries of Indonesia, Korea, the Philippines and Thailand. The sample periods are divided into two non-overlapping sub-periods namely; pre-crisis (1987Q1 – 1996Q4) and post-crisis (1997Q1 –2006Q4). Empirical results clearly suggest that CA Granger causes FA in these countries for the two sampling periods. Observations imply that causality patterns differ for each of the FA components with CA.